Societies Need New Perspectives on Race and Ethnicity: Societies in Harmony (Religious Context) - Ibrahim Kurt (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2021)
After many centuries, humankinds have reached today’s time by passing the centuries’ gatherings to their offspring. The civilizations which were established in the different part of the world have had their own culture according to their needs, religions, daily routines etc. One more step from here to cultural and traditional attitudes which were risen and had been started to show them on individual’s behaviors and ideas. During these periods, the individuals specifically have learned and understood life from their societies. So, individuals’ behaviors and attitudes are shaped according to societies what cultural arguments they have. The perception and understanding of arguments can be different in those many centuries but there have -always- been race and ethnicity. The interpreting of the terms specifically has shown itself weakly or strongly from the deep sight of the history till now. This article has a general glance at race and ethnicity for seeking and finding the middle path in the societies. It is important to study on race and ethnicity and to build a new understanding and perspective for humans and how to bring positive ideas for societies and nations.